Phycocyanin as Potential Natural Dye for its Use in Photovoltaic Cells - Enciso, Paula; Cabrerizo, Franco M.; Gancheff, Jorge S.; Denis, Pablo A.; Cerdá, María Fernanda (Journal of Applied Solution Chemistry and Modeling, 2013)
Phycocyanin, a blue protein extracted from Spirulina spp, shows promising characteristics that made it suitable for its use as natural dye in photovoltaic devices as the dye sensitized solar cells. In this work, a study of the aqueous solution-phase photochemistry, photophysics, spectroscopy, voltammetry and thermal stability of phycocyanin is presented. Suitable redox potentials (Eox = 1.2 V vs. Ag/AgCl) and a value of 1.96 V for E0,0 (i.e., the energy difference between the vibrationally relaxed levels of the first electronic excited state, S1, and the ground state, S0 of phycocyanin), allows the calculation of energetic profiles that in comparison with the conduction band of the anatase-TiO2 and I-/I3- electrolyte, could predict electron transfer with these components of the cell. The data reported herein should not only help to evaluate the potential use of phycocyanin as sensitizer for solar cells, but should also help in the development of novel solar cells where the photoinduced behavior of this protein can be controlled.